Immunodepression Induced by Thalidomide And Cyclosporine in the Heterotopic Heart Transplantation of Rabbits: Avaliation of Survival and Allograft Rejection - Carvalho, João Batista Vieira de; Petroianu, Andy; Travolo, Eduardo; Duarte, Alberto Brasil Barbosa; Oliveira, Benhur Heleno de (Brazilian Journal of Transplantation, 2004)
Introduction: In the present study we evaluated the immunodepressive action of thalidomide alone or in combination with cyclosporine on the prevention of rejection of heterotopic cardiac allografts in rabbits. Methods: Fifty rabbits were used, 25 of them as donors and 25 as recipients. Recipient animals were divided into five groups (n = 5 each): Group I (control) - non-immunodepressed animals; Group II, animals immunodepressed with cyclosporine at the dose of 10 mg/kg/day; Group III, animals immunodepressed with thalidomide at the dose of 100 mg/kg/day; Group IV, animals immunodepressed with cyclosporine at the dose of 5.0 mg/kg/day and Group V, animals immunodepressed with cyclosporine at the dose de 5.0 mg/kg/day in combination with thalidomide at the dose of 50 mg/kg/day. Heart donors were implanted in the abdomen of recipients. Results: The combination of thalidomide and cyclosporine showed the lowest histopathological rejection score (p < 0.05). Thalidomide administered alone or in combination with cyclosporine was effective against rejection, significantly increasing the survival (p < 0.01) of animals. Conclusion: Thalidomide should be considered as an effective immunodeppressive drug that play an important role in heterotopic heart allotransplantation in rabitts.